Сontrol system of education achievements of future economists in the process of stydying "higher mathematics" - Proshkin, Volodymyr (Continuing Professional Education: Theory and Practice, 2019)
The article represents a process of the control system application of future economists’ educational achievements in the process of studying «Higher mathematics», consisting the following stages: preparatory, informational and the main. It is noted that the leading idea of the system control is the establishment of the relationship between the teacher and the student on a subject-to-subject basis and the action coherence of each of them at all stages. It has been showed that the experimental work was carried out in the process of studying «Higher mathematics», which provides economic students with the necessary mathematical knowledge, forming skills and abilities to solve professional problems using mathematical methods and mathematical models. It is determined that the system implementation control process of educational achievements is based on the systemic, activity-based, modular and student-centered approaches. The role of the individual tasks for students’ independent work has been singled out. It should ensure the development of sustainable skills to use the mathematical apparatus in the problem-solving process, cognitive motivation formation, activity and independent work skills. Individual tasks accustom students to independent mental activity and ability to carry out it creatively. Moreover such tasks have an educational role. They strengthen the confidence in your own strength, bring a positive attitude to intellectual work and develop initiative and ingenuity. Method of calculating the rating in the proposed control system types has been defined. They are current rating; individual ratings on a certain credit module; semester rating; the overall rating within the discipline. The distribution of scores for the first and second modules of the discipline "Higher mathematics" for future economists has been presented. The next step will be the experimental verification of the control system of educational achievements of future economists in the process of studying mathematical disciplines in the University.